Aktivasi Deoiled Spent Bleaching Earth (DSBE) dengan Menggunakan Metode Ultrasonik untuk Mengadsorpsi Ion Logam Pb2+ - Helbianurramdan Helbianurramdan; Noor Hindryawati; RR Dirgarini Julia Nurlianti Subagyono (Jurusan Kimia FMIPA UNMUL, 2017)
Spent bleaching earth (SBE) as adsorbent of Pb2+ ion, through oil extraction process and continued by acid activation has been studied, this process assisted by ultrasonic wave in 30, 60 and 90 minutes reaction time. Based on the results analysis of X-Ray Flourescence (XRF), the reaction time of 30, 60 and 90 minutes showed an increase of SiO2 were 37.802 %, 42.374 % and 38,793 %. From the surface area with method methylene blue adsorption showed the surface area of DSBE-A 30, 60 and 90 were 34.3057 m2/g, 36.3375 m2/g and 35.8893 m2/g, respectively. XRD analysis showed the type of DSBE-A 60 was rectorite mineral with chemical compound was Na.Al4(Si,Al)8.O20.(OH)4.H2O and has a crystallinity 53.93%. Optimum conditions of DBSE-A 60 to adsorb Pb2+ ion in contact time was at 80 minutes, pH 3 and 20 ppm of Pb2+ ion concentration with adsorbtion efficiency up to 46.04 % and the optimum capacity of DSBE-A 60 to adsorb Pb2+ ion was 0.9209 mg/g.